Penilaian kemudahan pembelajaran, peruntukan kewangan dan kursus dalam perkhidmatan bagi kursus Pendidikan Islam di Politeknik Malaysia - Alias Mat Saad; Nik Mohd. Rahimi Nik Yusoff; Ruhizan Mohammad Yassin (Faculty of Education, Universiti Kebangsaan Malaysia, 2011)
The purpose of this study was to evaluate the learning facilities, financial allocation, in-service training to support the Islamic Education Courses in Polytechnic of Malaysia. The design of the study was a cross-sectional survey by using questionnaires to collect the research data. The respondents of the study were comprised of Polytechnics lecturers who were selected randomly. The findings showed that learning facilities, financial and in-service training are at the moderate level. Therefore, in order to maintain the quality of teaching and learning, the Polytechnic Administration should ensure learning facilities such as classrooms, teaching aids, financial allocation are in place and should be enhance to support the Islamic Education Courses. In addition to that, the Polytechnic should design their own in-service training to cater the current needs for the Polytechnic lecturers.